Solve te equation x*2=25, if x*y=2(x-1)(y-1)+1 and m=3.

Expert Answers
hala718 eNotes educator| Certified Educator

x*y= 2(x-1)(y-1)+1

To solve x*2 we will substitute y =2

x*2 = 2(x-1)(2-1)+1=25

x*2 = 2(x-1)+1 = 25

2x-2 +1 =25

2x-1= 25

2x= 26

x= 13

neela | Student

The given composition is x*y= 2(x-1)(y-1)+1 and m =3..

To solve  x*2 =25.

Under the composition , the LHS  x*2 = 2 (x-1)(2-1)+1 = 2(x-1)+1 = 2x-2+1 = RHS=25

2x-1 = 25.

x=(25+1)/2 =13

giorgiana1976 | Student

We'll substitute y by 2, in the expression of the composition law given:

x*2 = 2(x-1)(2-1)+1

WE'll open the brackets and we'll get:

2(2x-x-2+1)+1 = 25

2(x-1) = 25

2x - 2 = 25

We'll add 2 both sides:

2x = 25+2

2x = 27

We'll divide by 2 both sides:

x = 27/2

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question